2019
DOI: 10.1002/jcc.26021
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nonbonded Models for Metal Cations Using the Electronic Continuum Correction

Abstract: The parametrization of classical nonbonded models of metal ions has been widely addressed in the recent years. Despite the continuous development of novel and more physically inspired functional forms, the 12‐6 Lennard‐Jones plus Coulomb potential is still the most adopted force field in molecular dynamics (MD) codes, owing to its simple form and easy implementation. However, due to the integer formal charge, unpolarizable force fields of ions may suffer from overestimated interatomic electrostatic interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 62 publications
0
35
0
Order By: Relevance
“…This choice of partial charges, known as Electronic Charge Correction (ECC), was argued to be necessary in a nonpolarizable model to account for the electronic contribution to the dielectric constant. 45,46 ECC has received increased attention in recent years 24,29,[47][48][49] but remains unusual for most ion force fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This choice of partial charges, known as Electronic Charge Correction (ECC), was argued to be necessary in a nonpolarizable model to account for the electronic contribution to the dielectric constant. 45,46 ECC has received increased attention in recent years 24,29,[47][48][49] but remains unusual for most ion force fields.…”
Section: Introductionmentioning
confidence: 99%
“…Because this 12-6-4 LJ potential is not implemented in common MD packages, Nikitin and Del Frate recently optimized monovalent and multivalent ion parameters using the standard 12-6 LJ potential and ECC. 49 However, these ions were optimized in combination with the TIP3P water model and were shown to be poorly transferable to the TIP4P/Ew water model. Finally, Benavides et al 43 and very recently Zeron et al 44 produced the only ion parameters known to us specifically optimized for the TIP4P/2005 water model.…”
Section: Introductionmentioning
confidence: 99%
“…[15] and three different force fields: standard (i.e. non-scaled) Charmm36 [23] , scaled ECC- [24] and ECC2-Charmm36 [25] (for details see below). A force-switch modifier was used for the van der Waals forces and the Particle-Mesh-Ewald method [26] for the electrostatics.…”
Section: All Atom (Aa) Simulation Protocolmentioning
confidence: 99%
“…For the scaled ECC2-Charmm36 force field only the van der Waals radii of the ions changed compared to ECC-Charmm36. Here, in a previous study for Charmm36 developed ECC-ion-parameters were applied [25] . All ECC and ECC2 ion parameters are given in Table S1.…”
Section: Aa Simulation Setupmentioning
confidence: 99%
“…32,43,44 The importance of the ECC model manifests itself for both monovalent and multivalent ions, as they are capable of polarising their surrounding water molecules. 30,[45][46][47][48][49] Mason et al 46 and Pegado et al 50 showed that, predictions of the properties of aqueous salt solutions in the bulk improved significantly using the electronic continuum correction model compared with non-polarisable simulations. However, the applicability of the ECC model has not been fully examined for liquid-liquid and liquid-vapour interfaces.…”
Section: Introductionmentioning
confidence: 99%